2011
DOI: 10.1007/s00221-011-2973-8
|View full text |Cite
|
Sign up to set email alerts
|

Cervico-ocular coordination during neck rotation is distorted in people with whiplash-associated disorders

Abstract: People with whiplash-associated disorders (WAD) not only suffer from neck/head pain, but commonly report deficits in eye movement control. Recent work has highlighted a strong relationship between eye and neck muscle activation in pain-free subjects. It is possible that WAD may disrupt the intricate coordination between eye and neck movement. Electromyographic activity (EMG) of muscles that rotate the cervical spine to the right (left sternocleidomastoid, right obliquus capitis inferior (OI), right splenius ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
3
32
1
Order By: Relevance
“…Neck pain patients show sensorimotor disturbances that are often related to pain, diminished range of motion, quality of movement, and oculomotor disturbances (Storaci et al 2006;Treleaven 2008;Kristjansson and Treleaven 2009;Bexander and Hodges 2012;Kristjansson et al 2016;Stenneberg et al 2016). These oculomotor disturbances can provoke blurred vision, dizziness and the need to concentrate more than usual when reading (Treleaven and Takasaki 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Neck pain patients show sensorimotor disturbances that are often related to pain, diminished range of motion, quality of movement, and oculomotor disturbances (Storaci et al 2006;Treleaven 2008;Kristjansson and Treleaven 2009;Bexander and Hodges 2012;Kristjansson et al 2016;Stenneberg et al 2016). These oculomotor disturbances can provoke blurred vision, dizziness and the need to concentrate more than usual when reading (Treleaven and Takasaki 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Electromyography (EMG) studies have shown that not all dorsal muscles act synergistically as extensors; the splenius capitis muscle can activate during neck flexion in some healthy individuals (Keshner et al 1989) and higher levels of extensor muscle co-activation in neck pain have been reported (Lindstrom et al 2011). Surface EMG has demonstrated increased activity in superficial neck extensors in WAD (Bexander et al 2012, Juul-Kristensen et al 2013), but when controlling for differences in movement velocity, no differences were found between WAD and healthy controls (Vikne et al 2013). Small invasive EMG studies have reported decreased and less defined activity in the deep semispinalis cervicis muscle in WAD (Schomacher et al 2012), and the multifidus muscle was affected by eye movement (Bexander et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Surface EMG has demonstrated increased activity in superficial neck extensors in WAD (Bexander et al 2012, Juul-Kristensen et al 2013), but when controlling for differences in movement velocity, no differences were found between WAD and healthy controls (Vikne et al 2013). Small invasive EMG studies have reported decreased and less defined activity in the deep semispinalis cervicis muscle in WAD (Schomacher et al 2012), and the multifidus muscle was affected by eye movement (Bexander et al 2012). Both the expensive MRI and invasive EMG are difficult to apply in routine clinical practice and MRI does not provide information on the interplay between muscle layers.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired ventral neck muscle function with increased activity in the superficial SCM muscle and delayed activity in the deep muscles in neck pain (25,27) have been shown in WAD. Also in the dorsal neck muscles, increased activity in superficial neck extensors in WAD has been seen (28,45), but a study controlling for differences in movement velocity reported no differences between WAD and healthy controls (46). Two small studies have reported altered deep dorsal neck muscle function in WAD.…”
Section: Neck Muscle Functionmentioning
confidence: 99%
“…Two small studies have reported altered deep dorsal neck muscle function in WAD. A less defined and decreased activation in the semispinalis cervices muscle was reported (29) and the multifidus muscle was affected by eye movements (45).…”
Section: Neck Muscle Functionmentioning
confidence: 99%